Anthropological realities in different contexts: considerations of some topics in physical health - José Antonio Fernández de Rota Monter; María del Pilar Irimia Fernández (Universidad de Alicante, 1997)
In the present paper, the authors consider how Anthropology - by means of comparing different cultural contexts - could make us change our vision of some truths or dogmas such as health and illness, and could allow us to observe above all the real meaning of mental health. The authors discuss as well the various ways in which Anthropology could help in launching the concept of an holistic care, a humanistic concept capable of integrating social and cultural realities far from the positivist pattern of understanding the human being.